Formação de professores para uso da metodologia sala de aula invertida no processo de ensino a aprendizagem da gramática da língua inglesa no ensino fundamental II - Silva, Delanne Paulino da (2023)
English language teaching has demanded the use of methodologies and strategies that enable meaningful learning for students. Thus, understanding continuous education as a fundamental element to provide teachers with the opportunity to update their knowledge and acquire new skills and competencies, this research proposed to enable them to use the active methodology of Flipped Classroom (FC), as it expands the learning apportunities beyond the physical classroom, optimizes and personalizes the educational process (BERGMANN; SAMS, 2020; TALBERT, 2019; VALENTE, 2014, among others). The objective, therefore, was to understand the perceptions of teachers of a regular school regarding a training course aimed at implementing the FC in the teaching and learning process of English language grammar with students from Middle School. For this purpose, a qualitative (LUDKE, 1986; MINAYO, 2002; SOUZA; KERBAUY, 2017) and quantitative (SCHNEIDER, FUJII, and CORAZZA, 2017) approach was adopted, based on action research (FILLIPO; ROQUE; PEDROSA, 2021), designed following the stages of planning, action and reflection of an extension training course that used meta-training as a methodological proposal. Questionnaires, participant observation records, and analysis of materials produced by teachers during the training sessions were used as data collection instruments. Based on the analysis of the obtained results, it was concluded that the training course proved to be effective in empowering teachers to implement the flipped classroom in their real teaching contexts. Teachers recognized that careful planning and attention to some important details, such as the selection of grammar topics, defining learning objectives, and choosing learning strategies, are necessary for successful implementation of this methodology. Furthermore, the use of the FC as the course methodology provided valuable insights, highlighting the importance of developing an efficient feedback system, and the need to select materials that offer adequate support to teachers for carrying out tasks autonomously.